2021
DOI: 10.1038/s41598-021-81971-5
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics analysis of DNMT1 expression and its role in head and neck squamous cell carcinoma prognosis

Abstract: Head and neck squamous cell carcinoma (HNSCC) is the sixth most common type of malignancy in the world. DNA cytosine-5-methyltransferase 1 (DNMT1) play key roles in carcinogenesis and regulation of the immune micro-environment, but the gene expression and the role of DNMT1 in HNSCC is unknown. In this study, we utilized online tools and databases for pan-cancer and HNSCC analysis of DNMT1 expression and its association with clinical cancer characteristics. We also identified genes that positively and negativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 48 publications
3
11
0
1
Order By: Relevance
“…Recent studies showed that NSUN2 could promote tumour progression in HCC ( Sun et al, 2020 ) and gastric cancer ( Mei et al, 2020 ). Similar to our findings, Cui et al (2021) and Xue et al (2020b) found that DNMT1 played important roles in head and neck squamous cell carcinoma.…”
Section: Discussionsupporting
confidence: 93%
“…Recent studies showed that NSUN2 could promote tumour progression in HCC ( Sun et al, 2020 ) and gastric cancer ( Mei et al, 2020 ). Similar to our findings, Cui et al (2021) and Xue et al (2020b) found that DNMT1 played important roles in head and neck squamous cell carcinoma.…”
Section: Discussionsupporting
confidence: 93%
“…Recent studies showed that NSUN2 could promote tumour progression in HCC [37] and gastric cancer [38]. Similar to our ndings, Xue et al [39,40] found that DNMT1 played important roles in head and neck squamous cell carcinoma.…”
Section: Discussionsupporting
confidence: 91%
“…In breast cancer [ 56 ], high DNMT1 expression is significantly associated with poor survival ( p < 0.05) using multivariate analysis. However, head and neck squamous cell carcinoma (HNSCC) with advanced-grade tumors have high DNMT1 expression that is associated with better overall survival [ 57 ]. In our study, 4-year MSS in stage IV patients revealed that high ac-DNMT1 protein level, not DNMT1 protein expression, is a significant independent prognostic marker in a multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%